Fraud Voters Detection using Smart Electronic Voting Machine - Miss. Chavan Pallavi Ashok; Miss. Mane Priyanka Balasaheb; Miss. Kamble Aasavi Devappa; Shrenik Suresh Sarade (Journal of Electronic Design Engineering, 2018)
The main aim of this project is to provide secured identification and authentication processes for the voters and candidates by using fingerprint and face detection. The basic idea of this project is to make an electronic voting machine that will help to reduce the manual voting systems and prior versions of electronic voting. This system includes multiple layers of verifications to ensure the reliability of the device. every voter is entered into the system after being diagnosed and checked with the given database of enlisted electorate with together with fingerprint sensor and Pi camera.The final vote is then displayed onto a monitoring system for the satisfaction of voters. The voting problem is still critical in terms of safety and security. This project is about the design and improvement of a machine the use of fingerprint and face detection to offer a high performance with excessive safety to the vote casting gadget. Fingerprint is broadly used for identification. The proposed undertaking displays transparency and also carries the function of being self sustaining during the route of operation. Election is the act of party casting votes to choose on man or woman for some type of function. Election may additionally involve a public or private vote relying on the position. maximum of the positions like local, state, and federal governments are balloting on in a few form of election. An electronic voting system defines valid voting and gives a fast method of counting votes, which helps to conclude a final result. In this project, we propose an idea to avoid fraud voting and increases security about the voting. Lot of methods have been developed to avoid fraudulence in voting systems, but we are not able to reduce it completely. This system is secure, transparent, reliable as well as easy to use for the citizens. We scan the finger print and face of every individual. The scanned finger print is authenticated, If matches the individual is allowed to cast the vote.